ANALISIS SUDUT BELOK DAN KECEPATAN TERHADAP RADIUS BELOK MOBIL LISTRIK - Mara, I Made; Triadi, A. A. Alit; Rahmawan, Andrian Suci (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Mataram, 2023)
As the number of cars increases, the number of accidents that occur is directly proportional to the number of accidents that occur, namely 117,949 cases and this increases by around 8.3% annually, mostly due to driver negligence and lack of vehicle stability. One important aspect in car design is the steering system which influences the response of the vehicle's steering motion to steering wheel input and has a major influence on comfort as well as safety. The purpose of this study was to determine the turning radius at various speeds and turning angles and to determine the ratio of the turning angle to the turning angle of an electric car. In the analysis phase, calculations are carried out based on slip analysis to obtain the turning radius at various speeds and turning angles, and the ratio of the turning angle to the turning angle of the electric car. At the testing stage it is carried out by determining the steer rotation angle based on the specified turning angle. The results of this study are at a speed of 30 Km/hour with a turning angle of 240 resulting in the smallest turning radius, that is, in the analysis of 5.5 m and 5.75 m of experiment and the smallest percentage of turning radius, namely the results of the analysis are 4% smaller than the experimental results. At a speed of 50 Km/hour with a turning angle of 150 produces the largest turning radius, namely, in the analysis of 9.5 m and 9 m experiments and the greatest percentage of turning radius, namely the results of the analysis are 13% smaller than the experimental results. From the results of the analysis, the ratio of the turning angle to the turning radius is 18:1.